CCSP SNPA quick reference - Carroll, Brandon; Safari eBooks (Indianapolis, Ind. : Cisco Press, 2008)
As a final exam preparation tool, the CCSP SNPA Quick Reference provides a concise review of all objectives on the new CCSP SNPA exam (642-523).
Electronic reproduction.
Keywords: Firewalls (Computer security) -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books